2020
DOI: 10.1590/1984-3143-ar2019-0119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androgens and rutting season on drug metabolizing enzymes in dromedary camels

Abstract: A series of experiments were conducted to investigate the effect of rutting season on metabolism of testosterone (T) and its effect on drug metabolizing enzymes in dromedary camels. Serum and tissue samples were collected from liver, testes and poll glands of rutting and non-rutting camels treated with T at a dose of 0.5 mg/kg or 5α-dihydrotestosterone (DHT) at a dose of 0.2 mg/kg, given intramuscularly for 7 days. Liver samples were also used to monitor drug metabolizing enzymes. Testosterone and DHT concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Rutting camels showed elevated serum testosterone and 5α-dihydrotestosterone levels during breeding season as compared to other camels (29). There was elevated testosterone concentration in the plasma of testicular tissue in the breeding season (63)(64)(65).…”
Section: Enzymes Control the Camel Bull Behavior During The Rutting S...mentioning
confidence: 88%
See 1 more Smart Citation
“…Rutting camels showed elevated serum testosterone and 5α-dihydrotestosterone levels during breeding season as compared to other camels (29). There was elevated testosterone concentration in the plasma of testicular tissue in the breeding season (63)(64)(65).…”
Section: Enzymes Control the Camel Bull Behavior During The Rutting S...mentioning
confidence: 88%
“…In eliciting a behavioral response, 5α-DHT is more reactive than testosterone ( 31 ) which suggests that in the expression of hormonal effects testosterone metabolism could be an essential step ( 67 ). Greater activity of 5α-reductase was presumably expressed in testes and poll glands, resulting in higher DHT concentrations in rutting camels ( 29 ). In rutting season, histological examination of the poll gland suggested that the gland is endocrine ( 68 ).…”
Section: Enzymes Control the Camel Bull Behavior During The Rutting S...mentioning
confidence: 99%
“…The seasonal anatomical and histological findings in this study suggest increased secretory activity of the poll gland during rutting season as compared to non‐rutting season. El‐Khaldi and Homeida (2020) proved the increased secretory activity in the dromedary camel poll gland during rutting season. The poll gland secretion has been reported to contain androgens (Yagil & Etzion, 1980) and some types of pheromones (Skidmore, 2004) these hormones are believed to mark a mating area for the male in a certain herd.…”
Section: Discussionmentioning
confidence: 99%
“…The two poll glands are found subcutaneously behind the neck of male dromedary camel (Ebada et al., 2012; El‐Khaldi & Homeida, 2020; Ibrahim et al., 2020; Tingari et al., 1984). They yield a yellowish watery secretion with a characteristic offensive odour during the rutting season (Singh & Bharadwaj, 1978; Taha & Abdalla, 1980; Yagi & Etzion, 1980).…”
Section: Introductionmentioning
confidence: 99%